Correlation between the level of resilience and the quality of life of Ukrainian youth during the war - Sodolevska Валерія (Psychosomatic Medicine and General Practice, 2024)
Abstracts of the report to the IV Congress with international participation "Psychosomatic Medicine of the 21st Century: Realities and Prospects"